Shifting perceptions of social class: Race-based shifts in class-related occupations. Issue 3 (4th May 2021) - Weeks, Matthew
ABSTRACT: Based on social expectations associating White and Black racial categories with higher and lower ends of the social hierarchy, respectively, the criteria used in interpersonal judgments of social class categorizations should differ between White and Black targets, with Black targets needing objectively lower criteria than White targets to achieve a particular subjective level of social class. In an analysis of the occupations assigned to Working- and Middle-Class targets, respondents assigned occupations of higher financial and educational attainment, higher social status, more influence, and greater desirability to a White target than to a comparably described Black target. Despite this pattern, however, respondents judged the occupations assigned to a Black target as lower in prestige than those they assigned to a White target. The results are discussed in the context of interracial perceptions of social standing and motivations for societal change.